The Intercity Electric Railway Industry in Canada - Due, John, F. (Book collections on Project MUSE., 1966)
Professor Due's study presents first a general review of the development, characteristics, financial situation, and decline of the railway industry and then a brief history of each of the twenty-five companies which operated in the industry.